Serological and skin-test diagnosis of birch pollen allergy with recombinant Bet v I, the major birch pollen allergen. - Menz, G; Dolecek, C; Schönheit-Kenn, U; Ferreira, F; Moser, M; Schneider, T; Suter, M; Boltz-Nitulescu, G; Ebner, C; Kraft, D; Valenta, R (1996)
BACKGROUND: Type I allergy represents a severe health problem in industrialized countries where up to 20% of the population suffer from allergic rhinitis, conjunctivitis and allergic asthma bronchiale and in severe cases from anaphylaxis, leading to death. OBJECTIVE: The aim of this study was to evaluate recombinant Bet v I, the major birch pollen allergen for in vivo and in vitro diagnosis of birch pollen allergy. METHODS: A group of 51 birch pollen allergic patients and eight non-allergic control individuals were tested for birch pollen allergy by skin-prick and intradermal testing, comparing commercial birch pollen extracts with recombinant Bet v I. Quantitative and qualitative serological testing was done with natural and recombinant allergens by radioallergosorbent test (RAST), enzyme-linked immunosorbent assay (ELISA) and immunoblotting. RESULTS: Recombinant Bet v I allowed accurate in vivo and in vitro diagnosis of tree pollen allergy in 49/51 patients tested. No false positive results were obtained in any in vitro assay system (ELISA, Western blot) or by skin testing (skin-prick, intradermal test) with recombinant Bet v I. CONCLUSION: Our results document that recombinant Bet v I produced in bacterial expression systems allows accurate in vitro and in vivo diagnosis of birch pollen allergy in > 95% of birch pollen allergic patients.